Scientific justification of the co-extruded foodstuffs preparing method - A. A. Ospanov (Алматы технологиялық университетінің хабаршысы, 2021)
The article is devoted to the scientific substantiation of the optimal modes of the method of mechanical processing of flour poly-cereal mixtures prepared from whole-ground grain of cereals in the production of co-extruded food products. Functional thermostable fillings based on vegetable and animal raw materials for enrichment of products of a high degree of readiness increase the nutritional value and expand the range of finished poly-cereal products for therapeutic and prophylactic purposes. The novelty of the research is the acquisition of deeper scientific, technical and practical knowledge about the biologically active substances of co-extruded poly-cereal products of a high degree of readiness, about the enrichment of products with physiologically functional ingredients that have health-improving and prophylactic properties. The production of highly prepared poly-cereal products with fruit and berry and meat and dairy filling will help expand the range of new food products, improve the nutritional structure, strengthen health, and increase the immune defense of the human body.